Enzymatic determination of L(+) lactic and L(-) malic acids in wines by flow-injection spectrophotometry - Lima, José L. F. C. (2011)
A flow-injection system for the enzymatic determination of L( ) lactic acid and L(ÿ) malic acid in wines with spectrophotometric detection is described. The samples are dialysed in-line, and the enzymes in solution (malate dehydrogenase and lactate dehydrogenase) are injected as a train of plugs in the acceptor stream of the dialysis unit, yielding two peaks corresponding to the NADH formed for each determination. This methodology enables the determination of both acids with a single detector with a sampling rate of 20 h ÿ1 (0.4±3 g l ÿ1). The results are comparable to those obtained by the reference procedure, the repeatability is better than 5% (rsd), with low enzyme consumption (1.3 ml of suspension per sample).